Frequency of Musculoskeletal Pain Among Biomedical Science Students Working in Laboratory : Musculoskeletal Pain Among Laboratory Students - Anwar, Safa; Batool, Sana; Arif, Samia (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2021)
Objective: To find out the frequency of musculoskeletal pain and to identify risk factors among biomedical science students working in laboratory Methods: This cross-sectional study used Nordic musculoskeletal questionnaire among biomedical science students and was conducted in the university of Central Punjab and University of Lahore, Pakistan. Study sample comprised of 103 participants. Data was collected by using non-probability convenient sampling technique and was analyzed through SPPS v 21.0 Results: Out of 103 students reported a laboratory related musculoskeletal pain in the last 12 months while 16 (15.5%) within 7 days. The lower back (21.4% and 16.5%), neck (13.6% and 9.7%) and shoulders (10.7% and 6.8%) were the most common sites of problems reported within a 12 month and 7 day period respectively. Moreover, feeling of pain or discomfort in lower back, neck and shoulders prevented 18 subjects (17.4%) from performing daily activities while the 10 (9.8%) students required physical assistance during past last year. There was a statistically significant association between WMSP and gender, laboratory activity, and students work position Conclusion: It is concluded that significant number of university biomedical science students experienced musculoskeletal pain during their laboratory training activities which was found to be highly prevalent in upper extremities than lower extremities. Students reported work related musculoskeletal pain during the last 12 months respectively which has affected their daily activities. Few of them also seek medical advice by the health professionals. Students need education and awareness for better seating and safer work postures that may reduce the prevalence of musculoskeletal pain.